Femme battue et mari « batteur » : une reconstruction médiatique dans La Presse au XIXe siècle - Martel, Joane (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
We would assume that mass newspaperdom which is slowly introduced by the end of the XlXth century was tributary to the dominant conception of liberties which attributed rights to the householder and garanteed the privacy of the home. The evocation of these rights would then give rise to hesitations to intervene publicly in family quarrels. But, a documentary research of the Quebec daily La Presse reveals, on the contrary, that it proceeded to expose virulently cases of domestic violence in such a way that husbands became the main target of sarcasm. Therefore, unlike the ideological positions generally conceded to the Victorian project, the general tendancy to reduce the Victorian moralism to two main angles — being the purification of sexual behaviors and the promotion of a holy, asexual and family image of women — is questioned. The social project of the XlXth century appears more complex than what is generally thought since it proceeds not only to subject women but looks concurrently to “civilize” and moral-he the conduct of men.